2020
DOI: 10.1177/1465312520901725
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between craniofacial dimensions and genetic markers in ESR1 and ESR2

Abstract: Objective: To investigate the association of genetic markers in ESR1 and ESR2 with craniofacial measurements. Design: Cross-sectional study. Setting: School of Dentistry of Ribeirão Preto, University of São Paulo. Participants: A total of 146 biologically unrelated, self-reported Caucasian Brazilians with no syndromic conditions were included. Methods: Sagittal and vertical measurements (ANB, S-N, Ptm’-A’, Co-Gn, Go-Pg, N-Me, ANS-Me, S-Go and Co-Go) from lateral cephalograms were examined for craniofacial eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…While looking for other studies concerning the impact of ESR1 on the development of mandibular asymmetry, the study [29] was found. According to the authors of that study, the specific genetic variation in ESR1 (rs2234693 and rs9340799) and ESR2 (rs1256049 and rs4986938) represents possible markers for variation in the craniofacial dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…While looking for other studies concerning the impact of ESR1 on the development of mandibular asymmetry, the study [29] was found. According to the authors of that study, the specific genetic variation in ESR1 (rs2234693 and rs9340799) and ESR2 (rs1256049 and rs4986938) represents possible markers for variation in the craniofacial dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is also supposed that morphological variations of the sella turcica can alter the morphology of the pituitary gland and, consequently, cause variations in the hormones excreted by the pituitary gland (Kajear, 2015). In fact, hormones play an important role in craniofacial and tooth development (Omori et al, 2020;Spiller et al, 2020;Bergamo et al, 2021;Küchler et al, 2021;Reis et al, 2021). It is also possible that the connection between variation in the sella turcica and pituitary gland is through the genes that participate in the formation in both structures.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that the sella turcica is an intracranial bone depression located in the sphenoid bone that contains the pituitary gland (Tekiner;Acer;Kelestimur, 2015). The pituitary gland and the hormones excreted by it play an important role throughout the development and harmonious maintenance of the craniofacial complex (Omori et al, 2020;Spiller et al, 2020;Bergamo et al, 2021;Küchler et al, 2021;Reis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that other mechanisms could be involved in the variation of this expression, such as epigenetic factors and microRNAs, 45,46 or genetic polymorphisms in the encoding genes ESR1 and ESR2 . These polymorphisms could be involved in the variations of the receptor transcription, 47 what could affect the maxilla and mandible growth and development 48 . Although oestrogen levels do not regulate the expression of its receptors, it is important to emphasize that oestrogen‐regulated pathways involved in growth processes are mediated by direct interaction of this molecule with ERα and ERβ 49 .…”
Section: Discussionmentioning
confidence: 99%